2016
DOI: 10.1080/2162402x.2016.1242546
|View full text |Cite
|
Sign up to set email alerts
|

Lower incidence of acute GVHD is associated with the rapid recovery of CD4+CD25+CD45RA+ regulatory T cells in patients who received haploidentical allografts from NIMA-mismatched donors: A retrospective (development) and prospective (validation) cohort-based study

Abstract: To investigate the effects of non-inherited maternal antigen (NIMA) on clinical outcomes and immune recovery, especially of regulatory T cells (Tregs), in patients who underwent unmanipulated haploidentical transplantation. A retrospective cohort (n D 57) and a prospective cohort (n D 88) were included. All patients received haploidentical allografts from sibling donors. Reconstitution of immune subsets, including Tregs, was determined using multicolor flow cytometry. In the retrospective cohort, the cumulativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Our recent study also confirmed the Treg-dependent mechanism in lower GVHD incidence after NIMA-exposed donor HCT. 18 Impressively, the joint use of low-dose PTCy and ATG was safe in terms of engraftment, relapse prevention, or other adverse effects. Low-dose PTCy along with ATG and G-CSF did not influence haematopoietic recovery.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our recent study also confirmed the Treg-dependent mechanism in lower GVHD incidence after NIMA-exposed donor HCT. 18 Impressively, the joint use of low-dose PTCy and ATG was safe in terms of engraftment, relapse prevention, or other adverse effects. Low-dose PTCy along with ATG and G-CSF did not influence haematopoietic recovery.…”
Section: Discussionmentioning
confidence: 94%
“…15 Meanwhile, in G-CSF/ATG protocol, rapid reconstitution of Tregs has been demonstrated after non-inherited maternal-antigen (NIMA)mismatched donor HCT compared with non-inherited paternal-antigen (NIPA)-mismatched donor transplant, which translated into a lower incidence of acute GVHD after NIMAexposed donor HCT. 18 Based on the above findings, we postulate that lower-dose of PTCy could be sufficient for tolerance induction to warrant alleviating GVHD without compromising graft-vs.-leukemia (GVL) effect.…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have examined the relationships of immune components with outcomes in patients with hematological malignancies. [ 5 9 14 42 43 44 45 ] Fisher et al . [ 46 ] conducted a meta-analysis showing that high levels of regulatory T cells in the grafts were associated with improved OS, with a significant reduction in TRM and a reduced risk of acute GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the Baltimore experience with a cohort of patients undergoing MAC haplo-HCT using PTCy, MMF, and tacrolimus-based GVHD prophylaxis, Tregs achieved normal donor levels at all time-points examined (day +30, +90, +180, and +365) (181). Finally, in haplo-HCT using the GIAC protocol, patients with a higher day +30 percentage of naive Treg, defined as CD4 + CD25 + CD45RA + , had a significantly lower incidence of grades II-IV acute GVHD (191). This highlights the importance of reaching a satisfactory Treg reconstitution for the achievement of immune tolerance after haplo-HCT.…”
Section: Regulatory T (Treg) Cellsmentioning
confidence: 88%